(untitled) (Advances in Applied Mathematics and Mechanics, 2011)
In this work, we present and discuss some modifications, in the form of two-sided estimation (and also for arbitrary source functions instead of usual sign-conditions), of continuous and discrete maximum principles for the reaction-diffusion problems solved by the finite element and finite difference methods.